Law No. 12 of the year 2018 Amending Some Provisions of the Civil Aviation Law No. 28 of the year 1981 = قانون رقم 12 لسنة 2018 بتعديل بعض أحكام قانون الطيران المدنى الصادر بالقانون رقم 28 لسنة 1981 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic